A imprensa paulista na década de 1870: locus de divulgação e circulação de impressos - Da Silveira, Célia Regina [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2016)
This paper aims to consider the circulation of books and printed works in the Province of São Paulo based on the discussion which occurred in (and by) the newspapers concerning the context of the press and the readers in the Province of São Paulo, during the decade of 1870. After all, the newspapers were one of the main advertising vehicles of books and printed works, that is to say, they were one of the ways that made it possible to know the universe of the repertoire of printed works available to the readers. Besides this purpose, we seek to show, although partially, who were the booksellers and bookstores agents who appeared in the surveyed newspapers, in order to gather evidence of how the trade connections of printed works happened in the Province of São Paulo, in the mentioned decade.
The press in São Paulo in the 1870's: Locus of promotion and circulation of printed works
Keywords: Circulation of printed works; Cultural mediators; Newspapers of São Paulo